2018
DOI: 10.1016/j.canlet.2018.04.044
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional repressor Kaiso promotes epithelial to mesenchymal transition and metastasis in prostate cancer through direct regulation of miR-200c

Abstract: The loss of miR-200 family, through DNA methylation, results in cancer cells undergoing an epithelial to mesenchymal transition (EMT), and metastasis. In this study, we established that the transcriptional repressor Kaiso directly binds methylated regions of the miR-200 family, and this is reversed with 5-aza treatment. sh-Kaiso PC-3 cells display increased miR-200-a/b/c, miR-141, and miR-429 expression, with miR-200c demonstrating the most significant increase. Interestingly, overexpression of EGFR or treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 33 publications
(49 reference statements)
2
22
0
Order By: Relevance
“…Similar to findings in breast tumor cell lines, Kaiso depletion inhibited the proliferation of a glioma cell line accompanied by reduced expression of cell cycle regulators PCNA, CDK2, CDK4, Cyclin D1 and Cyclin E1 and increased expression of p21 and p27. Reduced expression of mesenchymal markers (Vimentin, N-cadherin) and increased expression of epithelial markers (E-cadherin) was also observed upon depletion of Kaiso in glioma cells [92], similar to what has been reported in both breast and prostate cancer cells [19, 83]. In addition to reinforcing Kaiso’s role as a regulator of EMT, these studies have also identified the miR-181 family as novel regulators of Kaiso expression.…”
Section: A Jack Of All Trades: the Multifaceted Functions Of Kaiso Insupporting
confidence: 70%
See 3 more Smart Citations
“…Similar to findings in breast tumor cell lines, Kaiso depletion inhibited the proliferation of a glioma cell line accompanied by reduced expression of cell cycle regulators PCNA, CDK2, CDK4, Cyclin D1 and Cyclin E1 and increased expression of p21 and p27. Reduced expression of mesenchymal markers (Vimentin, N-cadherin) and increased expression of epithelial markers (E-cadherin) was also observed upon depletion of Kaiso in glioma cells [92], similar to what has been reported in both breast and prostate cancer cells [19, 83]. In addition to reinforcing Kaiso’s role as a regulator of EMT, these studies have also identified the miR-181 family as novel regulators of Kaiso expression.…”
Section: A Jack Of All Trades: the Multifaceted Functions Of Kaiso Insupporting
confidence: 70%
“…PCa patients with Kaiso high and miR-31 low tumors had worse overall survival relative to patients with only Kaiso high tumors or miR-31 low tumors, suggesting that Kaiso promotes poor PCa survival via regulation of miR-31 expression. Most recently, Kaiso was also implicated in regulating the miR-200 family that suppresses EMT in PCa cells [19]. Upon Kaiso depletion in selected PCa cells, there was a significant increase of these miRNAs—similar to what was observed upon demethylation—and a decrease in downstream EMT targets such as ZEB1/2, Twist and Snail.…”
Section: A Jack Of All Trades: the Multifaceted Functions Of Kaiso Inmentioning
confidence: 76%
See 2 more Smart Citations
“…24 Kaiso promotes cancer metastases through direct regulation of epithelial-mesenchymal transition (EMT) genes and several other tumor-suppressor micro RNAs. 25 In breast cancer, overexpression of Kaiso in infiltrating ductal carcinomas (IDCs) was associated with loss of E-cadherin and increased cell migration and invasiveness. Depletion of Kaiso resulted in increased cell adhesion and development of small-sized primary tumors in in vivo and in vitro studies.…”
Section: Genetic Basis Of Health Disparitiesmentioning
confidence: 99%